Pengaruh Pelatihan, Motivasi, dan Lingkungan Kerja Terhadap Produktivitas Karyawan Pada PT. Angkasa Pura Indonesia Bandar Udara Internasional Soekarno-Hatta - Kintan Ulyantiputeri; Masruri Masruri; Abdillah Sani (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the effect of training, motivation, and work environment on employee productivity at PT. Angkasa Pura Indonesia (Persero), Soekarno-Hatta International Airport. In the increasingly competitive aviation industry, improving human resources is essential to support company performance. The research employed a quantitative method with an associative approach. The sample consisted of employees selected using simple random sampling. The research instrument was a questionnaire tested for validity and reliability, and the data were analyzed using multiple linear regression. The results show that training, motivation, and work environment have a positive and significant effect on employee productivity, both partially and simultaneously. These findings indicate that better training programs, higher work motivation, and a more conducive work environment lead to improved employee productivity. The practical implication highlights the importance for management to strengthen continuous training programs, establish effective reward and incentive systems, and create a healthy work atmosphere. This study is expected to serve as a reference for PT. Angkasa Pura Indonesia (Persero) and other companies in the same sector in formulating human resource development strategies to enhance competitiveness